Thermal Changes in Guidewires Used During Endoscopic Retrograde Cholangiopancreatography During Electrical Conductance: An Ex-Vivo Safety Experiment - Rahul Karna; Nicholas Michael McDonald; Jacob Weiner; Théodon I. Netoff; Stuart K Amateau (Endoscopy International Open)
The risks of pancreaticobiliary tissue damage secondary to electrical conduction along cannulation wires in the vicinity of electrocautery has rarely been independently studied and remains mostly a theoretical issue. We aimed to evaluate the heat generated by commercially available guidewires in the setting of currents used for sphincterotomy to assess their safety during endoscopic procedures. We tested heat generation from eleven common guidewires used in endoscopic retrograde cholangiopancreatography using an electrosurgical generator in combination with thermocouple temperature probe in an ex vivo model.Thermal changes during electrical conductance were nominal except for minimally wrapped 0.018” wires where the maximum change in temperature were 4.9° C with ENDO CUT Q settings and 6.8° C with ENDO CUT I settings. Also, the Glidewire 0.018” and the Visiglide 0.025” produced visible sparks along their distal ends with defects in the insulation found later under microscopic evaluation. In our ex-vivo study, minimal heat was generated via electrical conductivity despite direct current suggesting negligible risk of thermal injury during sphincterotomy.